Gun Violence in United States of America Systematic Reviews and Meta-Analyses - Karimu, Olusola O (Journal of Challenges, 2015)
The present study conducted systematic reviews and meta-analyses of relevant literature and data relating to gun violence in United States of America and found that the current concern about gun violence arises from a growing understanding of the adverse economic, physical, mental, and behavioral health effects that result from community exposure to high rates of gun violence. Therefore, it is noted that gun violence has become a major socio-economic and public health issues in United States of America due to the fact that it has eroded the quality of life of majority of the citizens. The study therefore established that interventions and strategies to address the problem of gun violence should address the intransigent causes of American gun violence - dying cities, inequality, deteriorating family structure, and the all-pervasive economic and social consequences of a history of slavery and racism that provides a generally acceptable strategy for reducing incidents of gun violence.